Evaluation framework for BIM-based VR applications in design phase. Issue 3 (13th May 2021) - Kim, Jung In; Li, Sining; Chen, Xingbin; Keung, Calvin; Suh, Minjae; Kim, Tae Wan
Abstract: The integration of building information modeling (BIM) and virtual reality (VR) has attracted increasing attention in the architecture engineering and construction (AEC) industry. Despite the rapid emergence of BIM-based VR applications, no evaluation framework specialized for the technologies exists in the AEC industry. After extensively reviewing existing studies and interviewing experts, the research team proposed an evaluation framework for BIM-based VR applications, which consists of 3 stages, 5 areas, 14 criteria, and 29 metrics and focuses on the design phase of the projects. To assess the usefulness of the framework, the team applied it to five BIM-based VR applications using a BIM-based design project for an educational building in Hong Kong. The team also interviewed experts to discuss the comprehensiveness of the framework. The results show that the framework provides consistent results for comprehensive evaluation criteria and metrics in a quantitative and flexible manner. Further research that considers additional criteria and/or metrics related to other phases (e.g. construction phase) is required to extend the framework to the whole lifecycle. Graphical Abstract: